Infant Brain Structural MRI Analysis in the Context of Thoracic Non-cardiac Surgery and Critical Care - Mongerson, Chandler R. L.; Wilcox, Sophie L.; Goins, Stacy M.; Pier, Danielle B.; Zurakowski, David; Jennings, Russell W.; Bajic, Dusica (Frontiers in Pediatrics, 2019)
Objective: To determine brain magnetic resonance imaging (MRI) measures of cerebrospinal fluid (CSF) and whole brain volume of full-term and premature infants following surgical treatment for thoracic noncardiac congenital anomalies requiring critical care. Methods: Full-term (n=13) and preterm (n=13) patients with long-gap esophageal atresia, and full-term naïve controls (n=19) < 1 year corrected age, underwent non-sedated brain MRI following completion of thoracic noncardiac surgery and critical care treatment. Qualitative MRI findings were reviewed and reported by a pediatric neuroradiologist and neurologist. Several linear brain metrics were measured using structural T1-weighted images, while T2-weighted images were required for segmentation of total CSF and whole brain tissue using the Morphologically Adaptive Neonatal Tissue Segmentation (MANTiS) tool. Group differences in absolute (mm, cm3) and normalized (%) data were analyzed using a univariate general linear model with age at scan as a covariate. Mean normalized values were assessed using one-way ANOVA. Results: Qualitative brain findings suggest brain atrophy in both full-term and preterm patients. Both linear and volumetric MRI analyses confirmed significantly greater total CSF and extra-axial space, and decreased whole brain size in both full-term and preterm patients compared to naïve controls. Although linear analysis suggests greater ventricular volumes in all patients, volumetric analysis showed that normalized ventricular volumes were higher only in premature patients compared to controls. Discussion: Linear brain metrics paralleled volumetric MRI analysis of total CSF and extra-axial space, but not ventricular size. Full-term infants appear to demonstrate similar brain vulnerability in the context of life-saving thoracic noncardiac surgery requiring critical care as premature infants.